2017
DOI: 10.1136/bmjopen-2016-011865
|View full text |Cite|
|
Sign up to set email alerts
|

Case characteristics among Middle East respiratory syndrome coronavirus outbreak and non-outbreak cases in Saudi Arabia from 2012 to 2015

Abstract: ObjectivesAs of 1 November 2015, the Saudi Ministry of Health had reported 1273 cases of Middle East respiratory syndrome (MERS); among these cases, which included 9 outbreaks at several hospitals, 717 (56%) patients recovered, 14 (1%) remain hospitalised and 543 (43%) died. This study aimed to determine the epidemiological, demographic and clinical characteristics that distinguished cases of MERS contracted during outbreaks from those contracted sporadically (ie, non-outbreak) between 2012 and 2015 in Saudi A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 18 publications
3
27
0
3
Order By: Relevance
“…The results of the present study are consistent with those of a Saudi Arabian study using Saudi Ministry of Health public data on MERS cases reported between September 2012 and September 2015, in which it was estimated that the mean time from symptom onset to confirmation was 6.60 days and the mean time from symptom onset to notification was 5.30 days (Alhamlan et al, 2017). The median time from symptom onset to confirmation was not reported in that study.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present study are consistent with those of a Saudi Arabian study using Saudi Ministry of Health public data on MERS cases reported between September 2012 and September 2015, in which it was estimated that the mean time from symptom onset to confirmation was 6.60 days and the mean time from symptom onset to notification was 5.30 days (Alhamlan et al, 2017). The median time from symptom onset to confirmation was not reported in that study.…”
Section: Discussionsupporting
confidence: 91%
“…The retrospective fatality rate varies between outbreaks, ranging from 36.5 to 60% [33,35,37,38,42]. The mortality rate of 20.4% observed for the Korean outbreak is probably the most reliable epidemiologically due to the comprehensive investigations carried out [34].…”
Section: Fatality Ratementioning
confidence: 99%
“…The first cases of infection with MERS-CoV were reported in 2012 [1]. Hospital-acquired MERS-CoV infections have been described worldwide and represented a third of all cases reported in Saudi Arabia in the early stages of the epidemic [1,32,33]. Clustered hospital-acquired infections were frequently observed during the first outbreaks and probably contributed to spreading the disease from the primary site of virus infection to the whole Arabian peninsula, the most striking example of hospital-acquired outbreak being the Korean outbreak in 2015 [34].…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong links between healthcare facilities and the spread of the MERS disease have been found in KSA, where the majority of patients were in contact with other patients at healthcare facilities [15][16][17][18]. Unfortunately, this phenomenon is widespread and well-known as nosocomial infections (hospital-acquired infections) which occur frequently with surgical-site infections (SSIs), pneumonia and gastrointestinal infections among the top hospitalacquired infections (HAIs) [19,20].…”
Section: Introductionmentioning
confidence: 99%